Watching Pornography Alone or Together: Longitudinal Associations With Romantic Relationship Quality. Issue 2 (17th February 2021) - Huntington, Charlie; Markman, Howard; Rhoades, Galena
Abstract: Pornography viewing has been cross-sectionally and longitudinally linked to poorer romantic relationship quality. However, only a few studies have looked at (1) the associations of changes in pornography viewing over time with relationship characteristics, (2) differential impacts of watching alone and watching with one's partner, and (3) how gender moderates these associations. The current study utilizes multilevel modeling to assess for between- and within-subject effects of watching pornography alone versus together on romantic relationship quality over time. A random national sample of 1, 234 individuals, who began the study in unmarried heterosexual romantic relationships of at least 2 months' duration, completed five waves of mail-in surveys over a 20-month period. Watching pornography alone was generally associated with poorer relationship quality for men (e.g., lower relationship adjustment and commitment, less emotional intimacy), but better relationship quality for women. People who reported watching more pornography with their partner reported more relationship intimacy and increases in watching together over time were associated with increases in sexual intimacy. Both watching alone and watching together were related to higher levels of psychological aggression between partners, with few differences by gender. Implications for sex education, relationship education, and couples therapy will be discussed.